DESIGN INFORMATION SYSTEM FOR UNIVERSITY OF DUHOK HOSTEL - Chiai Muhammad haji Al-Atroshi; Dina Rafaa (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This paper suggests a hostel management information system that can be used to administer University of Duhok Hostel. It shows the proposed database tables, user interfaces and functions required for this purpose. This information system will be used to manage the hostel rooms, floors, and various events. For the past few years, the number of students and the rooms accommodating them has increased incrementally. Hence, there is a lot of pressure on the person running the hostel as no special software or database are usually used in this context. This paper explores the drawbacks of the existing system and the requirements for designing a new computerized and more user friendly and graphical user interface (GUI) oriented system. Finally, the proposed system is implemented using a combination of Microsoft Access 2010 and visual basic, and the implementation results with their discussions are given in this article.